Strategi Pendidikan Kemandirian dan Keterampilan (PKK) dalam Membentuk Karakter Siswa di MI Nurul Huda Sedengan Mijen - Safira, Yuliana Dwi; El-Yunusi , Muhammad Yusron Maulana (Indo-MathEdu Intellectuals Journal, 2024)
Education in Indonesia has progressed along with the changing times. The changing times that are increasingly sophisticated require human resources to be more advanced. One way to create advanced human resources is to form human character as early as possible starting from elementary school with independence and skills education. The purpose of this research is to find out the objectives of Independence and Skills Education and what is carried out by schools in implementation. The research method used is a qualitative method. Data collection techniques use interviews, observations, and documentation. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the analysis show that the implementation of PKK at MI Nurul Huda Sedan Mijen has a positive influence in shaping the character of students, fostering traits such as responsibility, resilience, and creativity. These results underscore the importance of an education system that not only prioritizes academic achievement but also the cultivation of life skills and ethical values that are essential for the holistic growth of students. Recommendations are given to further strengthen the program, through increased collaboration with stakeholders and the integration of innovative teaching methods